Sarapataanguna Pre- and Post-Islamic Philosophy as the Philosophy of the Traditional House of the Buton People of the Walaka (EMARA: Indonesian Journal of Architecture, 2017)
Since the issuance of the "Ijtihad (command) Sultan" to the royal Sara (device), harmony and brotherhood (Sara Pataanguna) in Islam were manifested in the form of a typical Buton house. The royal Sara's and wood carpentry experts in the kingdom based on "Ijtihad Sultan" together performed ed deliberations. Deliberation aims to find a building form for the house, which follows the philosophy of Sara Pataanguna. In conventional Buton homes. The notion of significance and helpful ideals was embodied in both the pre-Islamic and post-Islamic Sara Pataanguna worldview. Based on the role-sharing functions, the Butonesse traditional house is divided into two types, houses of Kaomus / Walakas with public roles and houses of common Kaoumus / Walakas without public roles. This research aimed to analyze d the philosophy and symbolic meaning of the houses of the Kaomus / Walakas with public roles. The research used qualitative research with a case study approach. The result concluded that Sara Pataanguna became Walakas Butone 's traditional houses, especially for the owners who hold public positions because the Sara Pataanguna principles were contained in the meaning and function of the house symbols.